The influence of the electrodes spacing of a mapping catheter on the atrial voltage substrate map. Issue 5 (November 2018) - Mori, Hitoshi; Kato, Ritsushi; Ikeda, Yoshifumi; Goto, Koji; Tanaka, Sayaka; Asano, So; Shiki, Yuichiro; Nagase, Takahiko; Tahara, Mai; Iwanaga, Shiro; Muramatsu, Toshihiro; Matsumoto, Kazuo
Highlights: The voltage of close bipolar was significantly smaller than wide bipolar. The low voltage zone identified by close bipolar was significantly larger than wide bipolar. Low voltage zone ratio was also larger in close bipolar than that in wide bipolar. Larger low voltage zone was observed on the septal and posterior walls than the other areas. Abstract: Background: Detailed substrate mapping is important for catheter ablation. However, the influence of the electrode spacing of the mapping catheter on the substrate map has not been well clarified. The aim of this study was to investigate the influence of the electrode spacing of the mapping catheter on the voltage of the substrate map. Methods: Protocol 1 : We recorded the local atrial potentials of the left atrium (LA) using the ablation catheter during sinus rhythm in six atrial fibrillation (AF) patients. The voltage of each atrial potential was compared between a close-bipolar (1–2 electrode) recording and wide-bipolar (1–4 electrode) recording. Protocol 2 : Two voltage-maps of the LA were constructed separately using a 20-pole circular catheter and 10-pole circular catheter during sinus rhythm in 42 AF patients. The low voltage zone (LVZ) (<0.5 mV) areas obtained by 2 voltage maps using the 10-pole and 20-pole circular catheters were compared. Results: Protocol 1 : The close-bipolar voltage of the local potentials was significantly smaller than that of the wide-bipolar voltages (0.76 ± 0.39 mV vs. 0.63 ± 0.41 mV, p < 0.0001). Protocol 2 : The size of the LVZ areas identified by the 10-pole and 20-pole catheters was 1.12 ± 1.92 cm 2 (1.47 ± 2.78%) and 8.30 ± 7.80 cm 2 (8.83 ± 8.32%), respectively ( p < 0.0001). Conclusions: The voltage of the local atrial potential using the close-bipolar catheter was significantly smaller than that using the wide-bipolar catheter. Care should be given to the electrode spacing of mapping catheters when analyzing the voltage of the atrial myocardial potentials.